Internationalization of higher education: what underlies the discourse of UNESCO and OECD - Parra-Sandoval, Maria Cristina (Universidade Estadual de Campinas, 2021)
The internationalization of higher education is an issue and strategy that has become increasingly important in all countries of the world and international organizations linked to higher education. However, the process of internationalization is neither neutral nor are the policies that drive it. The university's traditional mission as a producer and transmitter of knowledge faces challenges linked to the pressure of political and economic power and the orientation of its narratives. The article seeks to reveal what underlies the UNESCO and OECD discourse and how this influences the process of internationalization of higher education and the policies that countries implement in this regard. The conclusion is that, in practice, these discourses are promoting a specific model from university to emulat.